Developing Students' Language Skills through Project-Based Teaching of the Languages for Specific Purposes - A Case Study - Маrijana M. Prodanović; Valentina M. Gavranović (University of Belgrade, Teacher Education Faculty, 2020)
Starting from the analysis of the legislation regulating the education system in the Republic of Serbia, and through the prism of the theoretical review of the project-based teaching as a model of interactive and innovative teaching, as well as the fundamental principles set out in the Common European Framework of Reference for Languages, this paper aims to explore what opportunities the project-based teaching provides for the purpose of strengthening students' language skills in the context of learning English for Specific Purposes, particularly English for Medical Profession at secondary level. Theoretical assumptions were tested empirically using a case study. The qualitative analysis showed that project-based teaching, a model placing students and their needs in the centre of the teaching process, is an effective didactic system that teachers can use in organising and implementing instruction that encourages the development of all language skills.